Pengaruh Promosi Di Media Sosial Dan Word Of Mouth Terhadap Keputusan Pembelian Di Kedai Ayam Djoeprek - Adinda Amelia Sari Nata Dawud (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research aims to determine the Influence of Promotion on Social Media and Word of Mouth on Purchasing Decisions at Ayam Djoeprek Shop. The type of research used is quantitative. The sample for this study is 98 buyers at Ayam Djoeprek Shop using nonprobability sampling techniques with incidental sampling, where the author will choose anyone unexpectedly or coincidentally, customers who come to Ayam Djoeprek Shop. The results of the study indicate that the variables Promotion on Social Media and Word of Mouth have a simultaneous effect on Purchasing Decisions. This is evidenced by the calculated F value of 40.417 and the critical F value of 3.09 with a significance value of 0.000 < 0.05. This research shows that the variables Promotion on Social Media and Word of Mouth have a positive and significant effect on Purchasing Decisions.